Case Report: The management of hemorrhagic shock of different origins by target-controlled coagulation and extracorporeal organ support (continuous renal replacement therapy) - Pertich, Ákos; Lovas, András (Frontiers in Anesthesiology, 2024)
Introduction: Trauma-related severe bleeding and peripartum hemorrhage complicated with shock state is challenging for acute care physicians. Management steps relating to one another include damage control surgery, maintenance of optimal clotting preconditions, point-of-care and targeted supplementation of coagulation factors, control of hyperfibrinolysis, and supplementation of thrombocytes. Extensive tissue damage and surgical management of bleeding activate the proinflammatory process, leading to a dysregulated immune response. The originating systemic inflammation produces further damage, harmfully altering clot formation through the activation of immunothrombosis.The case series presents one obstetric, massive bleeding patient and one politraumatized with severe hemorrhage. Both underwent extended surgery regarding bleeding control intervention.Elimination of coagulation disorder was driven by point-of-care viscoelastometry and targeted clotting factor supplementation. Continuous renal replacement therapy and hemadsorption technique augmented the well-established, up-to-date recommendations-guided care throughout the treatment line. Patients could leave the intensive care unit in 4 and eight days following the initial injury. Conclusion: Prompt administration of extracorporeal organ support enhanced the recovery from hemorrhagic shock.